(untitled) (African Journal of Biomedical Research, 2020)
There is limited data on disclosure of Paediatric HIV to significant others in the social network of children which may impact on their care. This study determined the prevalence of disclosure of Paediatric HIV to infected children and others as well as their impact on the children. It took place at the Paediatric Infectious Disease Clinic of the University College Hospital, Ibadan. Caregivers of HIV positive school aged children were interviewed using a semi-structured questionnaire and the Parent version of the Strength and Difficulties Questionnaire. Data was analysed using IBM SPSS Statistics version 20.0. A total of 200 children were studied with a male: female ratio of 1.3:1 and ages ranging from 6-17 years. Disclosure of HIV status had been done to 54 (27%) of the 200 children. Disclosure was not associated with a significant difference in psychological functioning or adherence to ART. Disclosure had been made to extended family members in 128 (64%) of the 200 patients, to the children’s siblings in 33 (21.4 %) of the 154 who had siblings, to the family spiritual leaders in 28 (14%) of the 200 families and to the children’s teachers in 3 (1.5%) of 197 cases in school. In response to disclosure, all the siblings, teachers and spiritual leaders encouraged the families and expressed willingness to support but this was so for only 108 (84.4%) of the 128 extended family members. Major forms of support given were financial, medication reminder, emotional support and prayers. Negative outcomes included stigmatization and HIV related parental separation. There is need for health workers to promote disclosure to significant others and provide support for families who get abandoned by relations following disclosure